Control of Southern root knot nematode Meloidogyne incognita (Kofoid and White) Chitwood on tomato using green manure of Fumaria parviflora Lam (Fumariaceae). (January 2015) - Naz, Ishrat; Saifullah,; Palomares-Rius, J.E.; Khan, S.M.; Ali, S.; Ahmad, M.; Ali, A.; Khan, A.
Abstract: Extracts of the plant Fumaria parviflora have demonstrated nematicidal properties and it is a potential novel control agent against plant parasitic nematodes. In this research, we examined the use of F. parviflora, in green house and field experiments, as a green manure against Meloidogyne incognita on tomato. M incognita did not parasitize F. parviflora as shown using a host pathogenicity test with a range of different inoculation rates of the nematode. Applications of F. parviflora 15 days before transplanting at the highest dose of 30 g fresh chopped whole plant material per kg of soil showed the most promising results. The root portion of F. parviflora showed higher nematicidal activity than the tops of the plant. All plant growth parameters studied were significantly promoted by the application of green manure in addition to the toxic effect on M. incognita . These data suggest that F. parviflora could be used alone or as part of an Integrated Pest Management strategy as a novel management tool for M. incognita . Highlights: Fumaria parviflora possesses tremendous nematicidal potential. Meloidogyne incognita did not parasitize F. parviflora as shown using a host pathogenicity test with a range of different inoculation rates of the nematode. In a green house studies, the application of F. parviflora 15 days before transplanting of tomato showed promising results against M. incognita and improved the plant growth parameters of tomato. Roots and tops of F. parviflora when applied as green manures effectively suppressed M. incognita on tomato in the green house and field trials. F. parviflora could be used alone or as part of an Integrated Pest Management strategy as a novel management tool for M. incognita .